Risk management and networks: How SMEs adapt to changing business environments via networking? - Pääkkönen, Emma (2018)
The aim of this qualitative research is to study what impacts global megatrends have in organizational context to SMEs, how SMEs are prepared for these changes with risk management and how networking aids SMEs to adapt to changing business environments. Moreover, the aim is to study how SMEs recognize and perceive potential threats arising from these changes. SMEs risk management practices are further examined against these megatrend-related impacts and how networks partake the different risk management stages. Empirical evidence for this research was gathered by conducting several rounds of semi-structured interviews with 11 informants. In addition, stakeholder analyses were employed to collect primary data. The research was implemented in South Karelia, Finland in the fall of 2017 spring 2018 and analyzed by using content analysis method. The results indicate that risk perception has a significant role mandating the nature of a megatrend-related change when recognizing and perceiving changes. Furthermore, the perception of global megatrend impacts varies significantly among case companies. In general, risk management practices in case firms are unsystematic and reactive. Moreover, networks offer an access to information and advice, which can be useful in different stages of risk management. However, the role of network utilization decreases when the risk management process progresses and the utilization of different stakeholders changes and decreases. Tämän tutkimuksen tavoitteena on selvittää mitä vaikutuksia globaaleilla megatrendeillä on organisatorisessa kontekstissa pk-yrityksille, miten muutoksiin on varauduttu riskienhallinnan avulla ja miten verkostot auttavat yrityksiä sopeutumaan muuttuviin toimintaympäristöihin. Sen lisäksi tavoitteena on tutkia miten pk-yritykset tunnistavat ja havaitsevat näistä muutoksista johtuvia mahdollisia uhkia. Pk-yritysten riskienhallintaa tutkitaan tarkemmin näiden megatrendeistä johtuvien muutoksien näkökulmasta ja miten verkostot osallistuvat riskienhallintaprosessin ...